Emerging role of lncRNAs as mechanical signaling molecules in mechanotransduction and their association with Hippo-YAP signaling: a review - Lin, Siyi; He, Xinyu; Wang, Ying; Chen, Yu; Lin, Aifu (Journal of Zhejiang University. B. Science, 2024)
Cells within tissues are subject to various mechanical forces, including hydrostatic pressure, shear stress, compression, and tension. These mechanical stimuli can be converted into biochemical signals through mechanoreceptors or cytoskeleton-dependent response processes, shaping the microenvironment and maintaining cellular physiological balance. Several studies have demonstrated the roles of Yes-associated protein (YAP) and its homolog transcriptional coactivator with PDZ-binding motif (TAZ) as mechanotransducers, exerting dynamic influence on cellular phenotypes including differentiation and disease pathogenesis. This regulatory function entails the involvement of the cytoskeleton, nucleoskeleton, integrin, focal adhesions (FAs), and the integration of multiple signaling pathways, including extracellular signal-regulated kinase (ERK), wingless/ integrated (WNT), and Hippo signaling. Furthermore, emerging evidence substantiates the implication of long non-coding RNAs (lncRNAs) as mechanosensitive molecules in cellular mechanotransduction. In this review, we discuss the mechanisms through which YAP/TAZ and lncRNAs serve as effectors in responding to mechanical stimuli. Additionally, we summarize and elaborate on the crucial signal molecules involved in mechanotransduction.